Electromagnetic lattice "invisibility" of the photon crystal made of magnetodielectric spheres in the form of octahedron - Kozar, A. I. (Eskisehir technical university, 2019)
Solution and analysis of a problem on electromagnetic lattice “invisibility” of the photon crystal made of magnetodielectric spheres in the form of octahedron with a cubic crystal lattice are presented.
Keywords: Electromagnetic lattice; Photon crystal; Magnetodielectric spheres; Octahedron